2015
DOI: 10.1038/srep18491
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-3 interacts with the ribosome and regulates c-Myc expression required for proliferation of chronic myeloid leukemia cells

Abstract: Kindlins are FERM-containing cytoplasmic proteins that regulate integrin-mediated cell-cell and cell-extracellular matrix (ECM) attachments. Kindlin-3 is expressed in hematopoietic cells, platelets, and endothelial cells. Studies have shown that kindlin-3 stabilizes cell adhesion mediated by ß1, ß2, and ß3 integrins. Apart from integrin cytoplasmic tails, kindlins are known to interact with other cytoplasmic proteins. Here we demonstrate that kindlin-3 can associate with ribosome via the receptor for activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…We first examined the expression of kindlin-3 in M10 melanoma cells. Kindlin-3 mRNA expression in M10 cells was minimal compared with K562 cells, a human chronic myeloid leukemia cell line that expressed kindlin-3, 36 whereas kindlin-1 and kindlin-2 were detected in M10 cells (Fig. 6A).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We first examined the expression of kindlin-3 in M10 melanoma cells. Kindlin-3 mRNA expression in M10 cells was minimal compared with K562 cells, a human chronic myeloid leukemia cell line that expressed kindlin-3, 36 whereas kindlin-1 and kindlin-2 were detected in M10 cells (Fig. 6A).…”
Section: Resultsmentioning
confidence: 97%
“…46 Kindlin-3 expression was reported to be up-regulated in late stage malignant breast cancer cells and promoted metastasis, 22 and it is involved in chronic myeloid leukemia cell proliferation. 36 However, another study reported kindlin-3 having a tumor suppressor function. 23 Kindlin-3 was reported to form a complex with EMM-PRIN and integrin ß1 in human M10 melanoma cells, suggesting that the protein is endogenously expressed in this cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Kindlin-3 was found to be associated with the pathology of chronic myeloid leukemia 96 and acute myeloid leukemia 95 . Qu and colleagues 96 showed that kindlin-3 may regulate the proliferation of human chronic myeloid leukemia K562 cells through the regulation of c-Myc protein expression and controlled the tumor growth of these cells in a xenograft model 96 . In another study, Wu and colleagues reported that levels of kindlin-3 increased in patients with acute myeloid leukemia after complete remission 95 .…”
Section: Association Of Kindlins With Cancermentioning
confidence: 99%
“…Although kindlin-3 is highly expressed in the hematopoietic system, there are only limited reports about its involvement in blood cell cancers, and a role of kindlin-3 phosphorylation in cancer cell is not known. Kindlin-3 was found to be associated with both acute and chronic myeloid leukemias (Wu et al, 2012;Qu et al, 2015). Kindlin-3 may influence proliferation of human chronic myeloid leukemia K562 cells through its regulation of c-Myc protein expression and kindlin-3 controlled the growth of these cells in a xenograft model (Qu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%